PUSAT PENELITIAN DAN PENGEMBANGAN KERETA API DI KOTA MADIUN MELALUI PENEKANAN ARSITEKTUR HIGHTECH SEBAGAI TAMPILAN BANGUNAN - Djadjang Godjali; Hari Yuliarso; Tri Joko Daryanto (Universitas Sebelas Maret Surakarta, 2014)
Abstract: The designing of Railways Research and Development Center are because of the developing of trains functions are not supported by improvment of technologies and human resources inside of railways system although trains have an important meaning for citizen’s mobility especially in Java and Sumatera Islands. There is caused by no adequate research and development center facility that integrated with railways educative and training center. Based from that reasons, there's important to provide an adequate research and development center facility that can be used for improving the new quality of train services from human resources and so the new technologies one. The activity of Research and Development Centre, basically are expandable activity that always grow and need the place that can accomodate it. Thus, Efficiency in Research and Development Centre’s activity is need a functional design too. So that, to accomplish that purposes, it needs a expandable function design’s building, more efficient and attractable design. So, from that reaseon, the primary of design’s problem is how to plan dan design an efficient, dynamic, attractive and expandable in the future though Hightech Architectural emohasis. The result is the design of Railways Research and Development Center’s building that applying Hightech Architectural Emphasis in Building Appearance. Keywords: Railways, Research and Development Center, Educative Tourism, Hightech Architecture